Overview of Ca2+ signaling in lung cancer progression and metastatic lung cancer with bone metastasis - Manh Tien Tran (Open Exploration Publishing Inc., 2021)
Intracellular Ca2+ ions that are thought to be one of the most important second messengers for cellular signaling, have a substantial diversity of roles in regulating a plethora of fundamental cellular physiology such as gene expression, cell division, cell motility and apoptosis. It has been suggestive of the Ca2+ signaling-dependent cellular processes to be tightly regulated by the numerous types of Ca2+ channels, pumps, exchangers and sensing receptors. Consequently, dysregulated Ca2+ homeostasis leads to a series of events connected to elevated malignant phenotypes including uncontrolled proliferation, migration, invasion and metastasis, all of which are frequently observed in advanced stage lung cancer cells. The incidence of bone metastasis in patients with advanced stage lung cancer is estimated in a range of 30% to 40%, bringing about a significant negative impact on both morbidity and survival. This review dissects and summarizes the important roles of Ca2+ signaling transduction in contributing to lung cancer progression, and address the question: if and how Ca2+ signaling might have been engaged in metastatic lung cancer with bone metastasis, thereby potentially providing the multifaceted and promising solutions for therapeutic intervention.